2018
DOI: 10.1007/s00056-018-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gingival recession after orthodontic treatment of infraversion and open bite

Abstract: PurposeAim of the present study was to investigate the prevalence of gingival recession and related factors in teeth with low occlusal function (open bite and infraversion) after orthodontic treatment.MethodsFrom January 2014 to December 2017, 403 patients received orthodontic treatment. Their gingival recession and related factors before and after treatment were retrospectively analyzed.ResultsThe prevalence of gingival recession in patients with infraversion and open bite after orthodontic treatment were 80.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
18
0
4
Order By: Relevance
“…[3][4][5] The presence of a thin GP has been associated with a greater risk for developing gingival recessions (GRs) 1,6 not only throughout a patient's lifetime, but also as a consequence of specific dental therapeutics such as orthodontic treatment. 7 Despite a lacking consensus of what treatment is truly superior for GT augmentation, or if the augmented thickness is sustainable over time, it has been shown that periodontal plastic procedures with the use of autogenous grafts (whether free gingival grafts [FGG] or connective tissue grafts [CTGs]) or substitutes (acellular dermal matrix [ADM] or collagen matrices [CM]) can significantly increase the amount of GT. [8][9][10][11][12][13] While previous reports have documented the relapse of recession treatment over time and the factors associated with it, 11,12,14 studies concerning the associated role of GT, its potential benefits with regard to gingival margin stability, periodontal/gingival health are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The presence of a thin GP has been associated with a greater risk for developing gingival recessions (GRs) 1,6 not only throughout a patient's lifetime, but also as a consequence of specific dental therapeutics such as orthodontic treatment. 7 Despite a lacking consensus of what treatment is truly superior for GT augmentation, or if the augmented thickness is sustainable over time, it has been shown that periodontal plastic procedures with the use of autogenous grafts (whether free gingival grafts [FGG] or connective tissue grafts [CTGs]) or substitutes (acellular dermal matrix [ADM] or collagen matrices [CM]) can significantly increase the amount of GT. [8][9][10][11][12][13] While previous reports have documented the relapse of recession treatment over time and the factors associated with it, 11,12,14 studies concerning the associated role of GT, its potential benefits with regard to gingival margin stability, periodontal/gingival health are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different methods have also been used for evaluating the GT that include transgingival probing, use of ultrasound, or a color‐coded probe 3–5 . The presence of a thin GP has been associated with a greater risk for developing gingival recessions (GRs) 1,6 not only throughout a patient's lifetime, but also as a consequence of specific dental therapeutics such as orthodontic treatment 7 …”
Section: Introductionmentioning
confidence: 99%
“…29 The types of orthodontic treatments were fixed appliances, 8,16,25,29,30 fixed appliances with premolar extraction, 8,27 functional appliances, 8 or not reported. 26,28 The selected articles reported various markers Amid et al of periodontal status as follows: gingival recession, 8,16,25,26,[28][29][30] probing pocket depth, 16,25 clinical attachment level, 16,25 inflammation, 8,16,25,26,28,29 periodontal index, 28 plaque index, 8,25,28,29 and keratinized tissue width. 16,25 One study reported gingival clefts, 27 but none of them reported on tooth loss, tooth mobility, or other adverse effects.…”
Section: Search Resultsmentioning
confidence: 99%
“…The evidence identified by this systematic review suggested that there might be an association between the gingival biotype and orthodontic treatment-induced periodontal complications. 16,25,[27][28][29][30] However, there are some limitations, including a limited number of studies, potential of bias, inconsistent methods for biotype determination, and various orthodontic interventions, making the comparison of the results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there is no consensus in the literature, orthodontic movement may facilitate the development of gingival recession, especially in cases where the movement of the dental elements occurs through an excessive force for vestibular or lingual / palatal. Therefore, it occurs the displacement of the dental root out of the proper positioning within the alveolar bone, which can generate regions of bone dehiscence and, potentially, gingival recession (Richman, 2011;Morris et al, 2017;Sharma et al, 2017;Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%